2022
DOI: 10.3390/en15207481
|View full text |Cite
|
Sign up to set email alerts
|

Grants and Funding for the Processes of Decarbonization in the Scope of Sustainability Development—The Case from Poland

Abstract: The study aimed to determine how the public perceives the directions of decarbonization to develop a sustainable energy strategy for Poland. The political challenge is to use dedicated funds and grants to move from the energy market to low-carbon technology. For sustainable development, governments must implement an environmentally friendly, cost-effective, and socially acceptable policy. The risk of social acceptance plays a vital role in Poland, especially in Silesia, influencing the decarbonization process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 99 publications
(120 reference statements)
1
3
0
Order By: Relevance
“…According to FMOLS, GDP also has a notable effect on CO 2 emissions. This fact is also confirmed in studies by other authors [2,4]. While this study does show that renewable energy's potential to minimize environmental consequences is promising, it also indicates that increasing the consumption of renewable energy has a considerable detrimental influence on ecological pressures.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to FMOLS, GDP also has a notable effect on CO 2 emissions. This fact is also confirmed in studies by other authors [2,4]. While this study does show that renewable energy's potential to minimize environmental consequences is promising, it also indicates that increasing the consumption of renewable energy has a considerable detrimental influence on ecological pressures.…”
Section: Discussionsupporting
confidence: 88%
“…Thermal power facilities using fossil fuels are the primary human-made sources of CO 2 emissions. The deterioration of the natural environment is the single biggest threat to the long-term viability of the human race [1,2]. Heightened levels of carbon dioxide in the atmosphere can be attributed mostly to human activity, including the combustion of fossil fuels such as oil, coal, and gas, as well as the widespread practice of deforestation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve the sustainable development, governments ought to implement cost-effective, environmentally friendly and socially acceptable policies. Czarnecka et al [40] identified socio-economic characteristics that influence the evaluation of the decarbonisation process in Poland. Respondents were those using central or local funds to conduct this process.…”
Section: The Renewable Energy In Polandmentioning
confidence: 99%
“…The adoption of energy-saving techniques and the expansion of the use of renewable energy sources are crucial [33]. However, these changes are also made possible by the presentation of modern advances and forms within the energy sector and the ceaseless quest for effectiveness and competitiveness [34]. The social transformation from energy consumer to prosumer poses both challenges and opportunities [35].…”
Section: Introductionmentioning
confidence: 99%